[PS 01-07] THE EFFECT OF GENES INVOLVED IN MONOGENIC HUMAN CARDIOMYOPATHIES IN A POLYGENIC MODEL OF CARDIAC HYPERTROPHY. (September 2016) - Prestes, Priscilla; Marques, Francine; Curl, Claire; Lewandowski, Paul; Delbridge, Lea; Harrap, Stephen; Charchar, Fadi
Abstract : Objective: Cardiac hypertrophy (CH) is the main risk factor for heart disease after age. Genetic factors are known to be involved, but their contribution is still poorly understood. We hypothesise that genes implicated in monogenic human forms of CH might also be involved in the more common polygenic forms of the disease. Our aim was to use the hypertrophic heart rat (HHR), a unique normotensive polygenic model of CH, to investigate mRNA expression of genes previously described to be associated with monogenic forms of dilated and hypertrophic cardiomyopathy in humans. Design and Method: We measured the expression of 37 transcripts with the TruSeq Targeted RNA expression kit using the MiSeq Desktop sequencer (Illumina) in left ventricles of HHR and its sister control strain, the normal heart rat (NHR), at five ages (2 days old, 4-, 13-, 33- and 50 weeks old). Results: We found only one gene ( Ttr ) differentially expressed in all age groups (FDR<0.1; P < 0.05). Ttr is involved in cardiac amyloidosis, infiltrating cardiovascular structures, leading to hypertrophy. However, in animals older than 13 weeks old, when CH is established in the HHR, we found four genes upregulated ( Actc1, Ankrd1, Cav3 and Fhl2 ). These genes are involved in a variety of muscle development pathways, growth and contractibility. Interestingly, Ankrd1 (fold change 1.3–2.47) has been described to be upregulated in the failing myocardium of dogs and in the left ventricles of patients with CH. Fhl2 is associated with cardiomyopathy in rats but seems to not be essential in cardiac development in mice. Conclusions: Our results show that genes involved in monogenic forms of human CH may also influence polygenic forms of the disease and deserve further investigation.